The impact of health beliefs, trust and attitude on consumers' intention to use cruise services after COVID-19 - Cao, Yangyi (Nanyang Technological University, 2021)
The cruise industry has suffered a huge loss due to the suspension of cruise operations during the COVID-19 pandemic. As the industry is preparing for recovery, there is an urgent need for research on cruise consumers’ psychology, in particular the factors influencing their intention to use cruise services after the pandemic. This study employs theories, namely, the health belief model, trust theory and attitude theory to investigate consumers’ use intention for cruise services after the pandemic. An online survey was administered to consumers in China’s tourism industry, where 376 responses were received. Subsequently, this study employs structural equation modelling to test its theoretical model consisting of hypotheses. The results show that consumers’ trust is directly influenced by health belief constructs including perceived safety threat, outcome expectation, self-efficacy and cues to action. Next, trust exerts a direct impact on consumers’ attitude and intention to use cruise services. Moreover, this study finds full and partial mediation effects. The findings provide a series of recommendations for cruise operators and policymakers in terms of marketing strategies, service design, public communication and health measures.